Penggunaan Istilah Jemaah dan Jemaah al-Muslimin: Analisis Dari Perspektif Ulama Turathi (Sains Humanika, 2018)
Jemaah is a term in political Islam that has been discussed since the early days of Islamic emergence and continue to be warmly discussed until now. This paper study meanings of ‘Jemaah’ and Jemaah al-Musliminin al-Qur'an, al-Sunnah and Muslims scholar’s perspectives. This study used documents analysis as its research methodology, especially analysis upon Islamic texts, works of Mufassirin and Muhadithin, classic and contemporary scholar’s views. The results showed that ‘Jemaah’ is an abbreviation of Jemaah al-Muslimin. This means, both concepts shared same meaning of terminology standpoint. This study also found that the meanings of Jemaah which was written by al-Shatibi are actually an adaptation of al-Tabari’s views. The Jemaah meanings are Islamic membership, majority of Islamic membership, a group of Islamic scholars and Prophet Muhammad’s companions. This paper also finds no obstacles for any organizations and Islamic groups calling them Jemaah and Jemaah al-Muslimin as long as there are no contradiction of its true meanings. In fact, this term has a solid backup in al-Sunna and used by earlier scholars. The denial of Jemaah usage is only based on concern of political hardlines’ existence in response to the loss of Islamic Caliph. This concern is fundamentally unable to deny its use because this term illustrates obligations of Muslims solidarity to unite and illegally divisive.
Keywords: Jemaah; Muslim solidarity; Islamic organizations; political Islam; Islamic thought.